2013
DOI: 10.5194/bg-10-1291-2013
|View full text |Cite
|
Sign up to set email alerts
|

CO<sub>2</sub> increases <sup>14</sup>C primary production in an Arctic plankton community

Abstract: Abstract. Responses to ocean acidification in plankton communities were studied during a CO2-enrichment experiment in the Arctic Ocean, accomplished from June to July 2010 in Kongsfjorden, Svalbard (78°56′ 2′′ N, 11°53′ 6′′ E). Enclosed in 9 mesocosms (volume: 43.9–47.6 m3), plankton was exposed to CO2 concentrations, ranging from glacial to projected mid-next-century levels. Fertilization with inorganic nutrients at day 13 of the experiment supported the accumulation of phytoplankton biomass, as indicated by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
119
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(130 citation statements)
references
References 82 publications
6
119
4
1
Order By: Relevance
“…Considerable day-to-day variations of up to 30% were observed in both fjord and mesocosms (Figure 6a). Based on data from all nine mesocosms, Engel et al [2013] showed that DOC increased significantly until nutrient addition; however, this may not be apparent from three mesocosms considered here. At the same time, Engel et al [2013] suggested that this might be attributed to contamination of samples during sample collection, transport, or instrument deployment.…”
Section: Maasmentioning
confidence: 59%
See 2 more Smart Citations
“…Considerable day-to-day variations of up to 30% were observed in both fjord and mesocosms (Figure 6a). Based on data from all nine mesocosms, Engel et al [2013] showed that DOC increased significantly until nutrient addition; however, this may not be apparent from three mesocosms considered here. At the same time, Engel et al [2013] suggested that this might be attributed to contamination of samples during sample collection, transport, or instrument deployment.…”
Section: Maasmentioning
confidence: 59%
“…Based on data from all nine mesocosms, Engel et al [2013] showed that DOC increased significantly until nutrient addition; however, this may not be apparent from three mesocosms considered here. At the same time, Engel et al [2013] suggested that this might be attributed to contamination of samples during sample collection, transport, or instrument deployment. For this reason, we did not estimate trends in DOC concentration but used average DOC values (over the course of experiment) for interpretation of other results assuming that potential methodological errors occurred randomly .…”
Section: Maasmentioning
confidence: 59%
See 1 more Smart Citation
“…Kim et al, 2006;Hopkinson et al, 2010;Riebesell et al, 2013;Paul et al, 2015;Bach et al, 2016;Bunse et al, 2016). Studies in the Arctic reported increases in phytoplankton primary productivity, growth, and organic matter concentration at CO 2 levels ≥ 800 µatm under nutrient-replete conditions (Bellerby et al, 2008;Egge et al, 2009;Engel et al, 2013;Schulz et al, 2013), whilst the bacterial community was unaffected (Grossart et al, 2006;Allgaier et al, 2008;Paulino et al, 2008;Baragi et al, 2015). These studies also highlight the importance of nutrient availability in the community response to elevated CO 2 , with substantial differences in primary and bacterial productivity, chlorophyll a (Chl a), and elemental stoichiometry observed between nutrient-replete and nutrient-limited conditions Schulz et al, 2013;Sperling et al, 2013;Bach et al, 2016).…”
mentioning
confidence: 99%
“…High CO 2 levels have been observed to have either no effect on abundance and productivity (Grossart et al, 2006;Allgaier et al, 2008;Paulino et al, 2008;Baragi et al, 2015;Wang et al, 2016) or increase growth rate and production only during the postbloom phase of an experiment (Grossart et al, 2006;Sperling et al, 2013;Westwood et al, 2018). Thus, bacterial communities appear to be relatively tolerant to ocean acidification, with bacterial growth indirectly affected by the ocean acidification responses of the phytoplankton community (Grossart et al, 2006;Allgaier et al, 2008;Engel et al, 2013;Piontek et al, 2013;Sperling et al, 2013;Bergen et al, 2016).…”
mentioning
confidence: 99%